Konseptualisasi Hak Cipta dan Hak Paten : Pengakuan dan Manajemen Risiko dalam Jaminan Kredit Perbankan dalam Hukum Indonesia - Muhammad Ismail (Dinasti Review Publisher, 2024)
In the international context, developments in banking law have recognized intellectual property as fiduciary collateral for applying bank credit. Likewise in Indonesia, although implementation has not yet occurred for several reasons. One of them is the issue regarding the economic assessment of intellectual property which is used as an object of collateral, risk management regarding its fluctuating value, and management of this intellectual property. Therefore, this research will discuss two legal issues, first, what is the role of intellectual property as credit collateral? Second, how is the normative implementation of intellectual property as collateral for obtaining banking credit? Thus, this research was written using an analytical approach in doctrinal legal studies. The resulting findings are that in a normative context, intellectual property has also been recognized as an object of collateral by being marked in the ratification of several international instruments, and implementation procedures have been regulated by the Director General of Intellectual Property and related banking regulations.